Hubungan Gejala Klinis (Demam, Pusing/Sakit Kepala, Nyeri Otot/ Sendi, Muntah, Perdarahan gusi) dengan Derajat Keparahan Infeksi Dengue - Nurlim, Risma; Haristiani, Ruris (Jurnal Kesehatan Pertiwi, 2022)
Introduction: The progression of dengue hemorrhagic infection varies on everyone. Assessing the severity of dengue degree as early as possible determine the patients prognosis and is required for adequate management, preventing shock and further bleeding. Clinical symptoms can be monitored and different in each degree of dengue so that it is can be used for vigilance and monitoring of dengue patients. Objectives: To determine the association between clinical symptoms with severity degree of dengue hemorrhagic fever. Method: This research was an analytic observational study with prospective cohort design at RSUD Sleman and RSUD Panembahan Senopati Bantul, DIY. Subject of the research was determined from medical records and anamnesis using questionnaire on the first day of hospital admission and following during treatment. Statistical analysis was used bivariate analysis following by multivariate analysis on variables that have p<0,05 with CI=95%. Result: Seventy-two patient were included in this study consisting of 46 severe dengue patients and 26 mild dengue patients. Severe dengue was most commonly experienced by the age of 19-65 years and male gender. The average of fever length is 4 days and hospitalization length are 6 days. Clinical symptom fever, headache, myalgia, arthralgia, petechiae, nose bleeding and bleeding gum are not significant with dengue degrees while vomiting (OR=16,434), were an association with dengue degrees. Conclusion: There is an association between clinical symptoms vomiting with dengue degree.